Promotional strategy design, to positioning Norte de Santander zone (Republic of Colombia) and Estado Táchira (Republic of Venezuela) (2011)
Tourism plays a decisive role in the economy of a region, its key elementis to connect the individual with their environment and this alsoallows improving the quality of life, creating a solid economic structureand contributing to economic and cultural development of peoples.The area covered by the Department of Norte de Santander, Colombiaand the Táchira State, Republic of Venezuela, has many attractions thatallow their development and positioning as a touristic destination.To achieve this goal is necessary to identify the strengths andpotentials of each of the municipalities, to analyze its real competitiveadvantage, establish a market segment that distinguishes them accordingto psychographic profiles and strengthen its positioning throughadvertising campaigns.The research is qualitative in nature, has an exploratory, descriptiveand explanatory.